PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PAK KELAS VII SMPN 1 KESU’ - Grace Estervine; Ayu Pranata Lia Bayu, Yenni Minggu (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
This writer was written because the authors found a lack of learning outcomes in class VII students in the subject of christian relegion education at SMPN 1 Kesu’. This research uses the car class action research ( PTK). Kemmis PTK model with four parts,namely: planning, implementaation, observation and reflection method by applying the Problem Based Learning model which aims to find out the increase in student leaning outcomes. based on the results of the research, it was found that the Problem Based Learning model can improve learning outcomes in PAK class VII subjects at SMPN 1 Kesu’